Perancangan Website E-Business dengan Metode Analisis SWOT dan PEST di Kedai S'Ajian Ndeso - Scholastica Lewoema; Arya Prayuda; Meizika Ayu Riski (LPPM Universitas Widya Dharma, 2023)
Currently, many business people take advantage of technological developments as a medium in the process of buying and selling, advertising, and disseminating information that can support progress in the business being run. Business design using technology (e-business) must pay attention to several important factors so that business systems can be realized in accordance with company goals. SWOT analysis is the most important analysis that must be considered in every business because this analysis will provide several points based on internal factors, namely strengths and weaknesses and external factors, namely opportunities and threats both from within and outside the company. Following up on the SWOT analysis, it would be better for companies/business actors to be able to analyze PEST which will explain how important political, economic, social, and technological factors are for a company. To be able to realize the solution from the previous analysis, we took the initiative to build a website using WordPress as the website builder. WordPress comes with open source and free properties that can be utilized by business people, especially MSMEs which are the object of our research. The application of e-business in the form of a WordPress website is expected to be able to keep up with the times and can provide benefits for related MSMEs. Keywords: E-Business, MSMEs, SWOT, PEST